Особливості неформального навчання засобами MOOC у закладах вищої освіти. - Шарова, Тетяна Михайлівна; Sharova, Tetiana; Землянська, Аліна Вікторівна; Zemlianska, Alina (My University, 2023)
UKR: Стаття присвячена особливостям неформального навчання засобами МООС у закладах вищої освіти. Акцентовано увагу на тому, що здобувачі освіти та науково-педагогічні працівники мають можливості безкоштовно викорис товувати онлайн-ресурси на закордонних платформах Udemy, Coursera, Edx, Alison. З՚ясовано, що кожен ЗВО має можливість у корпоративному доступі електронної пошти зареєструвати здобувачів освіти та науково-педаго гічних працівників для подальшої роботи на онлайн-ресурсах. Наголошено, що системна робота на онлайн-плат формах з метою проходження онлайн-курсів, дозволить українським користувачам використовувати платні ресурси на безоплатній основі, що є запорукою успішного навчання в дистанційному форматі.|||||||||| ENG :The article is devoted to the peculiarities of non-formal education by means of MOOC in the institutions of higher education. Attention is focused on the fact that students and scientific and pedagogical workers have the opportunity to use online resources on foreign platforms Udemy, Coursera, Edx, Alison for free. It was found that each institution of higher education has the opportunity to register students and scientific and pedagogical workers in the corporate e-mail access for further work on online resources. It was emphasized that the unique content with lectures, video materials, and test tasks allows you to get up-to-date information on professional development issues, as users have the opportunity to master new competencies, to immerse them selves in aspects of the professional growth of each user. It is indicated that the most interesting and relevant among users is the Coursera platform, which presents a significant number of online courses for improving qualifications and mastering new competencies. For institutions of higher education, a selection of courses with free access is another, based on the support of Ukraine during the state of war. The article reports that all users who take courses on the Coursera online resource can view their own achievements under the headings: online courses that are in progress or those that have been completed. Such filtering makes it possible to obtain information about which user՚s courses are in progress and which have already been completed. It is indicated that access to the Coursera online platform, for the purpose of further courses on a free basis, is possible after authorization and registration in the corporate mail of the institution of higher education. Attention is focused on the fact that in the conditions of the state of war in Ukraine, the possibility of non-formal education motivates students to study, since there is no attachment to a specific teacher or a certain schedule of calls to classes. It is emphasized that systematic work on the online platforms for the purpose of taking online courses will allow Ukrainian users to use paid resources free of charge, which is the key to successful distance learning
The peculiarities of non-formal learning through MOOC means in the institutions of higher education.
Keywords: неформальне навчання; МООС; онлайн-курси; заклад вищої освіти; безкоштовне навчання; масові відкриті онлайн-курси; non-formal education; online courses; institution of higher education; free education